Perbaikan Desain Mesin Pengering Kopra Sistim Tungku Vertikal: Upaya Produksi Kopra Berdaya Saing - Amheka, Adrianus; Nafi, Sulce I; Noach, Robert M.; K Alang, Jermias A. (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2018)
Implementation of this research has been carried out in the copra small industries "Bangun Mandiri" inKupang and aim to expand inter island marketing as one of community welfare. Outputs and outcomes are achieved suchas improving quality and quantity of white copra products through improved designs of multi-functional vertical furnacesystem copper dryers, especially in-house improvements, door frames, outer boxes and fireplaces as well as increasedcapital investment in the form of oven machinery; an increase in sales turnover of 30%; conducting Lab-scale researchfor possibility consuming dry coconut shells that have been patented as an additive of copra-scented foods/drinks andexpansion of marketing area through Pentahelix's partnership to accelerate inter island marketing. Measurable outcomeis to produce oven machine with complete design, also publication on scientific journal. In the future it is expected thatthe SMEs can further focus to quality control by involving academics or local government. To wake up consumerconfidence is also required efforts of local academics to periodically strive for program assistance activities andproduction management to make a teaching factory so that Pentahelix collaboration is established to produce smallindustries areas with highly competitive and prosper to the middle/lower communities and alleviate poverty, especiallykopra.